AB1116 Treatment of Patients with Moderate-To-Severe Systemic Lupus Erythematosus Disease Severity. (10th June 2014) - Strand, V.; Johnson, J.; Vandeloo, C.; Galateanu, C.; Lobosco, S.
Abstract : Background: Current treatments for systemic lupus erythematosus (SLE) include corticosteroids (CS); immunosuppressants (IM); antimalarials (AM); biologics such as belimumab, a monoclonal antibody that inhibits B-lymphocyte stimulator (BLyS) and received approval from the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) in 2011; and rituximab (off-label), a chimeric monoclonal antibody against B-cell CD20. Objectives: To assess the treatment of patients with moderate-to-severe SLE. Methods: Data were extracted from the Adelphi 2010 and 2013 Lupus Disease-Specific Programmes, multinational surveys of clinical practice. Physicians completed Patient Record Forms (PRFs), which included current treatment and treatment history, and underwent face-to-face interviews, which included questions about future treatment intentions. Patient eligibility was determined by physicians; disease activity and severity were based on physician assessment. Results: In 2010, data were collected from rheumatologists in the USA (n=50), France (n=23) and Germany (n=35), including 250/115/175 PRFs, respectively. The 2013 sample consisted of rheumatologists in the USA (n=97), France (n=37) and Germany (n=35), and included 550/200/207 PRFs, respectively. Within the moderate-to-severe SLE population, proportions of patients receiving each treatment class remained similar between 2010 and 2013; the most common being CS and AM (Fig. 1 ). Barriers to prescription of biologics included safety concerns, expense, and unwillingness of patients to attend infusion centres. In 2013, belimumab uptake was highest in the USA and Germany: treatment in moderate-to-severe patients was 14%/15%/6% in the USA/Germany/France, respectively. In the USA, belimumab was reported as a first-line therapy in 3% patients, and only 50% receiving it had received prior AM, IM and CS treatment (compared with 87% French and 83% German patients). 60% of physicians in the USA and 54% in Germany intended to increase belimumab use over the next 6 months, compared with 81% in France. Most physicians intended to maintain their use of rituximab; 26% of USA and German rheumatologists and 21% of French rheumatologists planned to increase it. Prescription of other treatment classes, including CS and AM, was predicted to remain unchanged. Conclusions: The treatment landscape of moderate-to-severe SLE has remained generally similar since 2010, with CS and AM remaining the dominant treatments despite FDA/EMA approval of belimumab. Belimumab uptake is evident in the US and Germany, but not in France, although a high proportion of physicians intend to increase its use over the next 6 months. In the USA, belimumab is prescribed earlier following diagnosis, sometimes as a first line therapy; use in Europe is later, following standard of care treatments. Acknowledgements: The authors acknowledge Costello Medical Consulting for writing and editorial assistance which was funded by UCB Pharma. Disclosure of Interest: V. Strand Consultant for: UCB Pharma, J. Johnson: None declared, C. Vandeloo Employee of: UCB Pharma, C. Galateanu Employee of: UCB Pharma, S. Lobosco: None declared DOI: 10.1136/annrheumdis-2014-eular.1829